Deteksi helicobacter pylori pada plak gigi dengan reverse transcriptionpolymerase chain reaction - Irene E. Riuwpassa; St. Rafiah; I Wayan S.A (Journal of Dentomaxillofacial Science, 2008)
Helicobacter pylori have been found associated with dental plaque. It was suggestedthat the oral environment may be one of the many potential pathways for theirtransmission. The aim of this study was to evaluate whether the oral cavity is apotential reservoir and possible sanctuary for Helicobacter pylori. Supragingival andsubgingival plaques were analyzed by a Helicobacter genus-specific reversetranscriptase-fragment was identified.